IMPROVE POETRY READING SKILL AND MOTIVATION OF STUDENT LEARNING THROUGH DEMOSTRATION METHOD - Faridah, Lilis; Mustika, Ika (JLER (Journal of Language Education Research), 2018)
The purpose of this research is to know (1) poetry reading skill of junior high school student using demonstration method compared with ordinary learning method. (2) learning motivation to read poetry using demonstration method compared with ordinary learning method. (3) the relationship between students' learning motivation and poetry reading skills. In this study the data were collected through observation on the implementation of student activity learning, questionnaire in the measurement of student learning motivation and poetry reading the test to measure poetry reading skill and pre-test and post-test to measure student's knowledge. The following data were analyzed using document analysis, data reduction, data presentation, and conclusion. The results of this study are (1) the reading skill of junior high school students whose learning using demonstration method is better than with ordinary learning. (2) learning motivation to read poetry using better demonstration method. (3) student learning motivation influences improvement in poetry reading skill.